LOAD FAKTOR PERALATAN PADA KAPAL CARGO TYPE LCT (Studi Kasus Kapal Lestari Abadi 03) - Zulfaidah Ariany (Diponegoro University, 2013)
This article titled is equipment load factor on cargo ship LCT type by taking a case study on Lestari Abadi ship03, the study aims to predict electric consumption calculation of LCT ship’s type which concerning with thenumber and type of generator; effective and efficience power consumption, safe and effective electric instalationand existing panel. So, minimum required output electric installed to Kapal Lestari Abadi 03 has to 150KW, asspecification performed by caterpillar C9TA 150KW, 188KVA, 1500rpm, 50Hz and 0.8.